Revenue bonds and an individual debt service ratio - Mateusz Klupczyński (Prawo Budżetowe Państwa i Samorządu)
Revenue bonds exist in the Polish legal system since 2000. So far only one local government unit decided to issue revenue bonds. The article presents the influence of revenue bonds on individual debt service ratio illustrated with an example of the City of Lublin. The author also makes an attempt to identify the causes of small practical interest in this financial instrument from the local government.